The enigmatic case of the genus Argyresthia in the Azores Islands (Lepidoptera: Argyresthiidae) - Santa-Rita, Jose V. Pérez; Baixeras, Joaquin; Karsholt, Ole (Zootaxa, 2020)
The species composition of the genus Argyresthia Hübner, 1825 in the Azores is examined. Argyresthia brumella, sp. nov., is described and illustrated from Terceira and Flores Islands. Argyresthia minusculella Rebel, 1940, syn. nov. and Tinea poecilella Rebel, 1940, syn. nov. are synonymized with Argyresthia atlanticella Rebel, 1940. The high variability of A. atlanticella is revealed through the polymorphic wing pattern and the intraspecific genetic divergence of the DNA barcode COI in the specimens examined.